Morphological revision of the Subgroup 1 Fauchald, 1970 of Marphysa de Quatrefages, 1865 (Eunicidae: Polychaeta) - Molina-Acevedo, Isabel C. (Zootaxa, 2018)
Fifteen species of Marphysa classified in the Subgroup 1 Fauchald (1970) were reviewed and evaluated in a morphological analysis of the subgroup. It was found that 13 of these have a characteristic morphological pattern distinct from that of Marphysa sensu stricto; as a consequence, a new genus is proposed, Paucibranchia n. gen. This new genus includes the species that have branchiae restricted to a few chaetigers in the anterior region, maxillae I with a rounded falcal arch and outer edge with a straight base plus a curvature in the basal inner edge, dorsal cirri longer in the branchial region and in media-posterior region as long or longer than pre-branchial chaetigers, and the postchaetal lobe in the branchial region well developed, elongated. Paucibranchia n. gen. includes six new species (P. andresi n. sp., P. carrerai n. sp., P. gathofi n. sp., P. gilberti n. sp., P. miroi n. sp. and P. patriciae n. sp.), two species not formally named, and other 13 species previously included in Marphysa (P. adenensis (Gravier, 1900) n. comb., P. bellii (Audouin & Milne-Edwards, 1833) n. comb., P. cinari (Kurt-Sahin, 2014) n. comb., P. conferta (Moore, 1911) n. comb., P. disjuncta (Hartman, 1961) n. comb., P. fallax (Marion & Bobretzky, 1875) n. comb., P. gemmata (Mohammad, 1973) n. comb., P. kinbergi (McIntosh, 1910) n. comb., P. oculata (Treadwell, 1921) n. comb., P. purcellana (Willey, 1904) n. comb., P. sinensis (Monro, 1934) n. comb., P. stragula (Grube, 1878) n. comb., P. totospinata (Lu & Fauchald, 1998) n. comb.). One species previously classified in the subgroup, Marphysa striata (Kinberg, 1865), was considered indeterminate. Finally, some statistical analyses on size dependent features and an identification key for species of the new genus were included.